VISUAL LEXICONS FOR VISUALLY IMPAIRED STUDENTS: A SEMANTIC INTERPRETATION ANALYSIS - Payana, Wita Dwi; Helmi, Rahil (ELTIN Journal, 2025)
This study explores how students who are blind from birth comprehend and form semantic concepts, focusing specifically on the notion of a "visual lexicon." By investigating the development and understanding of semantic concepts in these students, this study aims to reveal how blind students interpret meanings usually derived from visual experiences and adapt them through alternative sensory inputs. This is a descriptive qualitative study. The data were collected from observation and interview The data source of this research consists of 21 visual vocabulary words, categorized into three groups: nouns that can be touched, nouns that cannot be touched, and adjectives. The data of this research revealed that first and third-grade students use definitions and paraphrases in conceptualizing the semantics of visual vocabulary, while fifth and sixth-grade students use classification, naming, and definitions. In acquiring the semantic concepts of visual vocabulary, there is a shift from sight to hearing and touch. Since blind children lack visual input, their language acquisition, particularly in semantic concepts, relies solely on experiences conveyed through spoken information from others. Therefore, the study's results are expected to support curriculum development for language teaching tailored to blind students and contribute more broadly to educational and linguistic insights for the visually impaired.